Cross Sections for the \(^nat\)Zr\((p,xn)^89,90\)Nb Reactions Induced by 27.7 MeV Protons - Khue, Pham Duc; Do, Nguyen Van; Anh, Le Tuan (Communications in Physics, 2015)
The cross-sections for the formation of \(^89\)Nb and \(^90\)Nb radionuclides in proton induced nuclear reactions on zirconium were measured by using the well known activation method. The natural zirconium (\(^nat\)Zr) target and copper (\(^nat\)Cu) monitor foils were irradiated by 27.7 MeV proton beam at the MC50 Cyclotron of the Korea Institute of Radiological and Medical Science (KIRAMS), Korea. The induced gamma activities of the reaction products were measured by a coaxial high purity germanium (HPGe) detector coupled to a PC-based multichannel analyzer. The obtained cross sections for each nuclide are compared with those existing in literature and with the theoretical cross sections calculated by the TALYS - 1.4 code.